Tuning the helical sense and elongation of polymers through the combined action of the two components of tetraalkylammonium-anion salts. (August 2021) - Leiras, Seila; Suárez-Picado, Esteban; Quiñoá, Emilio; Riguera, Ricardo; Freire, Félix
Highlights: Two-step supramolecular interaction process of a PPA bearing an anilide pendant group with different salts of tetraalkylammonium anions. Chiroptical and colorimetric switch based on the interaction of a PPA with the two components of salts of tetraalkylammonium anions (anion = chiral switch, cation= colorimetric switch). Colorimetric thermometer based on an H bonding interaction between the anion of a tetraalkylammoniun salt and the acidic hydrogen of anilide group at the PPA pendant, which can evolve at different temperatures from a supramolecular hydrogen bonding interaction to deprotonation of the anilide group. Abstract: The helical sense and elongation of a helical polymer that bears the 4-ethynylanilide of ( R )-α‑methoxy-α-phenylacetic acid [m-( R )-1 ] can be tuned by the action of the two components of tetraalkylammonium-anion salts. Thus, while the supramolecular PPA-anilide/anion interaction creates a chiroptical switch, inducing either P or M helical senses in the poly(phenylacetylene) (PPA) depending on the nature of the anion — P helix: fluoride ( F − ) or cyanide (CN − ); M helix: acetate (OAc − ), benzoate (OBz − ) or azide (N3 − )—, deprotonation of the anilide group by these anions in dry conditions makes it possible to play with the elongation of the PPA, depending on the size of the tetraalkylammonium group, which results in a colorimetric switch. Thus, a color change from yellow to deep red is obtained by deprotonation of the anilide group when a tetraabutylammonium salt is used, while yellow/light-red and yellow/orange color changes are obtained when the size of the tetraalkylammonium group is reduced. Structural and mechanistic studies confirm that the color change occurs when the counterion accommodates itself close to the pendant group once the anilide hydrogen is removed. This PPA/tetraalkylammonium association is responsible of elongation changes in the PPA and therefore on the conjugation of the polyene backbone that is accompanied with color changes. Moreover, this colorimetric switch also operates in the solid state and can be switched in a vacuum/air moisture cycle. Graphical abstract: Image, graphical abstract